Sex cord tumor of the ovary, with tubular ring component and retroperitoneal metastasis: a case report and literature review - Jerónimo, José (2015)
We report the case of a patient who underwent 15 years ago to removal of right ovarian tumor at another institution, admitted to the gynecology by a tumor apparently dependent gynecological sphere. Exploratory laparotomy showed a tumor in the bladder and other retroperitoneal surface attached to the vena cava. The pathological study reported that both were metastatic ovarian TCS-TA. The pathology Iáminas surgery performed 15 years earlier was revised, confirming that corresponded to the same entity.